2022
DOI: 10.3390/joitmc8010043
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Protection by Face Masks during COVID-19: The Application of Customer Open Innovation

Abstract: This research investigated consumers’ purchase intention and preferences for face masks during the COVID-19 global pandemic. The Theory of Planned Behavior (TPB) was used as the theoretical framework. Empirical data (with 215 valid responses) were collected nationwide from the United States via Qualtrics Panel services. Exploratory factor analysis, confirmatory factor analysis, structural equation modeling, and multi-group comparison (chi-square difference) were used to estimate construct validity and test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…These factors can be readily translated to the public through the scientific community and were used due to the availability of data and may represent some of the important factors that consumers consider before purchasing respiratory protection. Consumers have expressed intent to purchase based on protection or comfort 5 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors can be readily translated to the public through the scientific community and were used due to the availability of data and may represent some of the important factors that consumers consider before purchasing respiratory protection. Consumers have expressed intent to purchase based on protection or comfort 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, some of these practices continued even after NIOSH-approved respirators became available and the public continued to wear alternatives. Consumers are habitual in nature, regardless of the current need or requirement for respiratory protection 5 . If another airborne disease or SARS-CoV-2 variant emerges, consumers may resume their practice of wearing non–NIOSH-approved respirators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research completed after the SARS and swine flu pandemics found that individuals with higher anxiety were more likely to use precautionary measures such as washing their hands and wearing masks [24][25][26]. Liang et al [27] investigated consumers' attitudes toward aesthetics, functional and social attributions, and subjective norms regarding purchase of face masks as a precautionary action during a pandemic. Results showed that participants' functional attributions and subjective norms were positively related to their intention to purchase face masks, but not aesthetics and social attributions.…”
Section: Individual Difference Variables and Use Of Precautionary Mea...mentioning
confidence: 99%